Free-Standing N-Doped Porous Carbon Fiber Membrane Derived From Zn–MOF-74: Synthesis and Application as Anode for Sodium-Ion Battery With an Excellent Performance - Xue, Kaiwen; Si, Yechen; Xie, Shuya; Yang, Jingxuan; Mo, Yan; Long, Baojun; Wei, Wen; Cao, Peiyu; Wei, Huixian; Guan, Hongyu; Michaelis, Elizabeth G.; Guo, George; et al. (Frontiers in Chemistry, 2021)
It is important to develop new energy storage and conversion technology to meet the energy crisis for the sustainable development of human society. In this work, a free-standing porous nitrogen-doped carbon fibers (PN-CFs) membranes were obtained from the pyrolysis of Zn-MOF-74/polyacrylonitrile (PAN) composite fibers, which were in-situ fabricated by electrospinning technology. The resulting free-standing fiber can be cut into membrane disks and directly used as anode electrode without the use of any binder or additive. The PN-CFs showed great reversible capacities of 210 mAh g−1 at current density of 0.05 A g−1 and an excellent cyclic stability of 170.5 mAh g−1 at current density of 0.2 A g-1 after 600 cycles in sodium-ion batteries (SIBs). The improved electrochemical performance of PN-CFs can be attributed to the rich porous structure derived by incorporated Zn-MOF-74 and nitrogen doping to promote the sodium ions transportation.